2003
DOI: 10.1046/j.1365-2044.2003.03235.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of personal, environmental and biological exposure of paediatric anaesthetists to nitrous oxide and sevoflurane*

Abstract: SummaryPaediatric anaesthetists are at higher risk of exposure to waste anaesthetic gases, which often exceed set safety limits. Recommended personal diffusive sampling techniques for monitoring exposure to waste anaesthetic gases may not give a true profile of exposure and hence biological sampling may also be necessary. We evaluated the exposure of paediatric anaesthetists to nitrous oxide and sevoflurane as assessed by personal environmental and biological samples. The influence of venue and technique, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Mean (SD) length of time in clinical anaesthesia was 12 (7.2) years, with 156 (53%) having ‡ 10 years' clinical experience. One hundred and fiftyfive (52%) respondents performed four or more paediatric sessions per week and the median (IQR [range]) number of sessions was 4 (2-6 [1][2][3][4][5][6][7][8][9][10][11][12]). Attitudes to the use of nitrous oxide are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean (SD) length of time in clinical anaesthesia was 12 (7.2) years, with 156 (53%) having ‡ 10 years' clinical experience. One hundred and fiftyfive (52%) respondents performed four or more paediatric sessions per week and the median (IQR [range]) number of sessions was 4 (2-6 [1][2][3][4][5][6][7][8][9][10][11][12]). Attitudes to the use of nitrous oxide are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Control of Substances Hazardous to Health (COSHH) Regulations 1999 state that 'exposure to anaesthetic agents must be reduced to as low as reasonably practicable' [1]. Previous studies have shown exposure to waste anaesthetic gases during paediatric operating lists to be high, especially during inhalational induction [2] and also in non-theatre areas [3] where paediatric anaesthetists may frequently operate.…”
mentioning
confidence: 99%
“…Raj and et al N 2 O pollution of operating room. Anesthesia said that scavenging system could be effective system was considered as one of the most on the rate of N 2 O pollution and contact of effective factor in the research (8). Also, the this gas.…”
Section: Resultsmentioning
confidence: 99%
“…to restore visibility), is therefore accompanied by the release of sevoflurane vapor. Hence, it is an additional source of waste anaesthetic gas (WAG) pollution [59,60,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Known sources of WAG pollution include leakage from the patient's mask, from endotracheal coupling, from loose tube fittings and from air exhaled by the patient in the recovery room.…”
Section: Discussionmentioning
confidence: 99%